2019
DOI: 10.1002/tal.1676
|View full text |Cite
|
Sign up to set email alerts
|

Damage assessment of reinforced concrete columns retrofitted by steel jacket under blast loading

Abstract: SummaryIn this study, the damage to a reinforced concrete column retrofitted by steel jacket subjected to blast loading was investigated. Actually, this research is an extensive study of the previous works of the authors. Therefore, some of finite element modeling and validation procedure were adopted. Extensively, the effect of the steel jacket used for retrofitting the reinforced concrete column was evaluated. The effects of scaled distance, axial compressive force, and steel cover plate thickness on the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Column damage is shown in Figure 23. Thai et al [70] modeled in LS-Dyna RC steel jacked columns (25 cm × 25 cm × 360 cm) and observed the influence of steel thickness, scaled distance, and longitudinal compressive force on the behavior of the columns under the blast load. The columns are designed according to Eurocode 2.…”
Section: Parametersmentioning
confidence: 99%
“…Column damage is shown in Figure 23. Thai et al [70] modeled in LS-Dyna RC steel jacked columns (25 cm × 25 cm × 360 cm) and observed the influence of steel thickness, scaled distance, and longitudinal compressive force on the behavior of the columns under the blast load. The columns are designed according to Eurocode 2.…”
Section: Parametersmentioning
confidence: 99%
“…[ 5 , 6 , 7 , 8 ] have performed analytical studies by using a SDOF and MDOF structural dynamic analysis to study the response of reinforced concrete columns under blast loads. In addition to this a numerical assessment on RC columns prone to blast loads are also evaluated by [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. [ 9 , 10 ] evaluated the damage propagation of RC column strengthened by steel jacketing and also predicted the residual strength of a FRP retrofitted RC column subjected to blast loading.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this a numerical assessment on RC columns prone to blast loads are also evaluated by [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. [ 9 , 10 ] evaluated the damage propagation of RC column strengthened by steel jacketing and also predicted the residual strength of a FRP retrofitted RC column subjected to blast loading. Thai et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thai et al [ 14 ], used a commercial FE analysis code to study the behavior of 250 × 250 × 3600 mm rectangular concrete columns retrofitted with a steel jacket under blast loading having scale distances from 0.10 to 0.40 m/kg 1/3 . The effects of the axial force and the steel thickness on the blast performance of the specimens were investigated.…”
Section: Introductionmentioning
confidence: 99%